Increasing security for RC4 algorithm by using PUF-based random number generators - Sahib, Naji Mutar; Abed, Hazim Noman; Ahmed, wasan Saad (International Journal of Engineering and Technology, 2018)
Rivest Cipher 4 (RC4) algorithm is the considerably stream cipher, and can be used of internet protocols. There is a quantity of weaknesses bytes even after the first 256 rounds (the size of the RC4 permutation) of the Pseudo random generation algorithm (PRGA). So far various modified RC4 research were presented but all of them have either ordinary privacy or accomplishment evaluation challenges. This paper introduces enhanced RC4 algorithm depending on Physical Unclonable Function (RC4 - PUF) which has solved both of these challenges. The principal development of the proposed RC4 - PUF methodology is that the changing of the s array reorganized to rely on the creation of a specific hardware random generator Method (HRGA) and the proposed methodology outcomes as follows:Output = Plaintext XOR generated key XOR random values from HRGA.The outcome of the tests demonstrates the refinement of the privacy of ciphers (average secrecy), randomness and accomplishment assessment (Encryption time and throughputs) over the variable key length and miscellaneous plaintext size of the proposed encryption RC4 â€“ PUF methodology.Â